Kyrgyz Republic Economic Update No. 7, Spring/Summer 2018 : Favorable Headwinds Time for Structural Reform - World Bank Group (World Bank, Washington, DC, 2019)
Economic growth was robust in 2017, above expectations. This was thanks to favorable external developments in the region, continued expansionary fiscal policy, and growth in the gold sector. Real GDP growth reached 4.6 percent in 2017, up from 4.3 percent in 2016, and the fastest rate since 2013. During the first 4 months of 2018, growth slowed to 1.3 percent, from a year earlier, as a result of the contraction in gold production; excluding gold, output grew at 2.5 percent, up from 2.3 percent over the same period in 2017. In short, the economy appears to have fully recovered from the recent shock brought about by the fall in oil prices. Investment and consumption drove output growth last year. Sources of growth appear to have been balanced. Growth was mainly driven by consumption and investment, with: private consumption growth returning to positive territory, after two consecutive years of contraction and high rates of public and private investment. Net exports also made a positive contribution, thanks to robust export growth. With the regional downturn now over, it is time the authorities should seize the opportunity for fiscal reform. First and foremost, action is required on the fiscal side to increase discipline and policy quality, transparency and consistency. In the past years, the authorities have deliberately delayed planned fiscal consolidation to accommodate the external shocks. As a result, public debt has remained elevated and fiscal buffers have been depleted. Moreover, fiscal discipline (in the context of relaxed targets) has been achieved at the cost of ad hoc measures, which entail reduced spending efficiency. It is now time to reverse this trend through implementing the recently adopted fiscal rule, tax administration reform and concrete measures to contain recurrent spending (to preserve room for investment). Additional steps to improve spending quality, include ensuring that planned amendments to the Public Procurement Law safeguard best international practice and that steps are taken to improve public investment management. In the long run the core challenge is to increase overall productivity in the economy. Creating and preserving fiscal space for investment in infrastructure is key, including via reforming energy tariffs. Significant long-term payoffs can also be expected from implementing the ambitious digital agenda under the Taza Koom flagship program. The Special Focus section of this report highlights the main challenges the country will face in this regard.